Salt intake is persistently reduced by emphasized warning: Long-term results of a controlled trial. Issue 3 (2017) - Markota, Nina Pinjuh; Rumboldt, Mirjana; Tomičić, Marion; Markota, Ivica; Rumboldt, Zvonko
No abstract available